Moving with the Screen on Zoom: Reconnecting with Bodily and Environmental Awareness - Loussouarn, Claire (The International Journal of Screendance, 2021)
Rather than seeing Zoom as a replacement for practicing movement and dance in a shared physical space, I propose to consider our relationship with the screen on Zoom as a movement in its own right. Using my experience of teaching movement on Zoom, I ask how we can connect with another via the screen without losing awareness of our bodies and the space which we're in. I argue that Zoom is a place of 'moving selfies' in dialogue where we can engage critically with the screen by practicing seeing with the whole body and moving with diffuse awareness and where we can critically reflect on our own habits of framing the world and its biases.